2012
DOI: 10.2319/061311-390.1
|View full text |Cite
|
Sign up to set email alerts
|

Apical root resorption during orthodontic treatment

Abstract: ; Hans-Gö ran Grö ndahl d ABSTRACT Objective: To investigate the incidence and severity of root resorption during orthodontic treatment by means of cone beam computed tomography (CBCT) and to explore factors affecting orthodontically induced inflammatory root resorption (OIIRR). Materials and Methods: CBCT examinations were performed on 152 patients with Class I malocclusion. All roots from incisors to first molars were assessed on two or three occasions. Results: At treatment end, 94% of patients had $1 root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 35 publications
9
110
0
5
Order By: Relevance
“…All these studies confirm the reliability and accuracy of the high resolution 3D images of the cone beam and show how valuable it is as a tool for detecting resorption 3,21,24,28 .…”
Section: How To Detect Oiirr: Input From the Cone Beamsupporting
confidence: 48%
“…All these studies confirm the reliability and accuracy of the high resolution 3D images of the cone beam and show how valuable it is as a tool for detecting resorption 3,21,24,28 .…”
Section: How To Detect Oiirr: Input From the Cone Beamsupporting
confidence: 48%
“…1 The incidence of OIRR is greater than 90%, 2 and the prevalence of minor to severe OIRR ranges from 94% to 6.6%, respectively. 3 It has been reported that 6.6% of the orthodontic patients in one study 3 had at least one tooth with OIRR greater than 4 mm. Micro-computed tomography (micro-CT) analysis is the current gold standard for the quantification of RR.…”
Section: Introductionmentioning
confidence: 99%
“…22 Other in vivo studies further confirmed that slanted apical root resorption could be evaluated only on tomographic images and was found in up to 15% of palatal root surfaces investigated. 1 In this study, the simulation of root shortening contained no slanted apical root resorption, and most moderate root shortening was more easily detectable on periapical radiography than the CBCT method as it could offer an overall view of the apical lesion. For the moment, we tentatively put forward that CBCT could not replace periapical radiography, which remains the primary imaging modality for detecting orthodontically induced EARR.…”
Section: Radiography Is the Most Important Tool For The Diagnosis Of mentioning
confidence: 98%
“…Monthly root shortening was greater after 6-month control than before. 1 In a separate study, clinically significant resorption was found for 74% of the centrals and 82% of the laterals, and apical root resorption was thought to be correlated with treatment duration and premolar extraction. 2 The process of root resorption in the permanent teeth is usually pathological, resulting in loss of dentin, cementum, or bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation